Mourning and melancholy: a comparative study on Christopher Okigbo and Dambudzo Marechera - Akcay, Ahmet Sait (School of African and GenderStuds, Anth and Ling, 2020)
This study explores the modernist subjectivity in Africa by revisiting two major poets, Christopher Okigbo and Dambudzo Marechera. It argues that the modernist self is created in the form of melancholy and mourning. The main question is to see how the African modernist subjectivity is constructed through poetry. As subjects of colonialism, both Okigbo and Marechera sought to establish new links combining them with the mainstream Euromodernist movement along with their own spiritual roots. In the sense of the construction of a modernist self, the main predicament they have to challenge is the Western knowledge system which infiltrated into mindsets through colonial dominion. Thus, Okigbo and Marechera enact a certain type of positionality strategy to claim their own poetic utterance. By invoking natural and spiritual images the poets demonstrate their affiliation to their roots. The process of mourning, here, becomes a passage through which the poets claim their strong allegiances to their roots. The sense of absence leads the poets to mourn their remote past or culture. The poets' relation with the past determines the dynamics of subjectivity. The idea of the past is so tempting and tantalising in many ways.